Exploring Cultural Conflict Resolution through Face Negotiation Theory in the Indonesian Film ‘Tarung Sarung’ - Adnjani, Made Dwi; Madrah, Muna Yastuti; Mujib, Ahmad (Jurnal The Messenger, 2023)
Introduction: This study examines Islamic values and intercultural communication through the lens of Face Negotiation Theory (FNT) in the film ‘Tarung Sarung’ (‘Sarong Fighting’). As a medium of communication, film delivers embedded messages that influence audience perceptions and emotions. ‘Tarung Sarung’ reflects societal realities and conveys messages that foster understanding across cultures. Indonesia's cultural diversity often leads to conflicts rooted in stereotypes, highlighting the need for cultural approaches to conflict resolution. Methods: This study employed a qualitative descriptive approach to explore how cultural values and communication strategies are portrayed in the film ‘Tarung Sarung.’ The research design included textual and visual analysis of selected scenes and dialogues reflecting intercultural communication and conflict resolution. Stella Ting-Toomey’s Face Negotiation Theory (FNT) was applied to interpret key themes such as individualism versus collectivism and face concerns. Findings: The analysis reveals that the film illustrates how cultural values shape individuals' approaches to conflict resolution. Through its characters, the film demonstrates how intercultural strategies are influenced by cultural backgrounds, emphasizing the importance of understanding cultural differences. Originality: The study contributes novel insights by applying FNT to analyze ‘Tarung Sarung,’ showcasing its depiction of Islamic values and intercultural communication in media. It underscores the role of film as a medium for fostering cross-cultural understanding.